Insights on biorational potential of Ocimum gratissimum essential oil and its binary combination with monoterpene phenol for control of rice weevil (Sitophilus oryzae) and aflatoxigenic fungi. - Remesh, V. Archana; Raveendran, Ashika; Bincy, K.; Wagh, Vasudev S.; Dastager, Syed G.; Babu, C. S. Vivek (Food Bioscience, 2022)
Food grain storage is a difficult task due to insect infestation and subsequent mycotoxin contaminations which adversely affects the nutritional quality of grains and leading to economic loss. Current research focuses on contact and fumigant toxicity effects of essential oils (EO) and aroma compounds against Sitophilus oryzae and growth inhibition of aflatoxigenic fungi. The EO of Ocimum gratissimum comprised of thymol (46.8%), gamma-terpi-nene (14.04%) along with o-cymene (11.76%). Also, Cymbopogon flexuosus rich in citral (76.3%) and geraniol (84.6%) and Cymbopogon nardus having geraniol (49.24%) and geranyl acetate (20.9%) were all evaluated using a dose of 25 mu L (Conc-833.3 mu L/L air) against S. oryzae. All the compounds showed significant mortality (>95%) at 24 h of exposure. The insecticidal property of O. gratissimum oil chemotype showed a strong contact and fumigant toxicity against S. oryzae at a highest dose of 25 mu L (Conc-833.3 mu L/L air) within 24 h. It has been further evaluated on three aflatoxigenic fungal strains which showed reduction in growth and aflatoxin content (Aflatoxin B and G), which was markedly reduced upon the treatment. The binary mixture interaction of O. gratissimum oil with monoterpene phenol (carvacrol) was assessed and the specific binary mixture of 80:20 ratio (having additive property) acts as a contact insecticide with 100% mortality. Hence, essential oil of less explored Ocimum species (O. gratissimum) and its binary mixture could be deployed as potential biorational for control of rice weevil (Sitophilus oryzae) and aflatoxigenic Aspergillus spp.
Keywords: Aflatoxigenic fungi; Binary combination; Essential oil; Ocimum gratissimum; Sitophilus oryzae